Yttrium fluoride nanomaterial, preparation method and application thereof, and negative electrode material for lithium-ion battery
Through solvent thermal method and calcination purification method, yttrium fluoride nanomaterial with good rod-like structure was prepared, which solved the high energy consumption and safety hazards of the existing metal fluoride preparation methods, and provided efficient electrochemical performance support for the negative electrode materials of lithium-ion batteries.
Patent Information
- Application Number
- CN202310373036.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-04-07
- Publication Date
- 2025-04-25
- Estimated Expiration
- 2043-04-07
AI Technical Summary
The existing metal fluoride preparation methods have high energy consumption, environmental pollution and safety hazards, and there are few researches on the application of rare earth metal fluoride in lithium-ion battery negative electrode materials.
The yttrium source and the fluorine source were reacted by a solvent-thermal method at 100 to 140°C to obtain the yttrium fluoride nanomaterial to be purified, and calcined and purified at 240°C to prepare a yttrium fluoride nanomaterial with a good rod-like structure.
This method realizes the preparation of yttrium fluoride nanomaterials at lower temperatures, reducing energy consumption, improving product purity and crystallinity, and providing excellent electrochemical properties for lithium-ion battery anode materials.
Smart Images

Figure CN116514155B_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of nanomaterials, and specifically relates to an yttrium fluoride nanomaterial, a preparation method and application thereof, and a negative electrode material for a lithium ion battery. Background Art
[0002] As a new type of energy storage device, lithium-ion batteries are widely used in electric vehicles, small electronic devices, large power grids and other fields. With the development of the technology field, the performance requirements for high-energy-density lithium-ion batteries are gradually increasing. The main factor affecting the energy density of lithium-ion batteries is the electrode material. At present, the methods to improve the performance of lithium-ion battery electrode materials mainly include nano-scaling the structure of electrode materials, composite carbon materials with excellent performance, and modification by coating or doping.
[0003] Based on the special properties of fluorine-containing compounds, they have a wide range of applications in the field of lithium-ion batteries. For example, fluorination of the positive electrode material of the battery or coating and doping with fluoride can significantly improve the electrode's resistance to HF corrosion and oxidation resistance. Fluorine-containing electrolyte lithium salts have high ionic conductivity in different solvent systems, outstanding comprehensive performance, and good commercial prospects. However, there are currently few studies on the application of fluorine-containing compounds in negative electrode materials for lithium-ion batteries. In particular, there are few studies on the application of rare earth metal fluorides as negative electrode materials for lithium-ion batteries. The reason for this phenomenon may be that the existing preparation methods of metal fluorides are highly dangerous. At present, the commonly used method for synthesizing metal fluorides is to use a high-temperature solid-phase method, that is, to mix the metal precursor and the fluorine source and calcine them at extremely high temperatures. The solid-phase method consumes a lot of energy and has environmental pollution problems. In addition, due to the high calcination temperature, it has a high safety hazard in large-scale production. Summary of the invention
[0004] In order to solve all or part of the above problems, one of the objects of the present invention is to provide a method for preparing yttrium fluoride nanomaterial, comprising:
[0005] At least a yttrium source and a fluorine source are subjected to a solvothermal reaction at 100 to 140° C. to obtain a yttrium fluoride nanomaterial to be purified;
[0006] The yttrium fluoride nanomaterial to be purified is calcined at 240° C. to 400° C. in a protective atmosphere to obtain the yttrium fluoride nanomaterial.
[0007] The second object of the present invention is to provide yttrium fluoride nanomaterial prepared by the above preparation method.
[0008] The third object of the present invention is to provide the application of the yttrium fluoride nanomaterial in the preparation of lithium ion batteries.
[0009] A fourth object of the present invention is to provide a negative electrode material for a lithium-ion battery, wherein the negative electrode material comprises the yttrium fluoride nanomaterial.
[0010] Compared with the prior art, the present invention has at least the following beneficial effects:
[0011] (1) The preparation method provided by the present invention uses a solvent thermal method to obtain yttrium fluoride nanomaterials at a relatively low temperature, and calcination at a relatively low temperature is used to purify and remove impurities to improve the purity of the product and increase the crystallinity of yttrium fluoride. Compared with the solid phase synthesis method, the preparation method provided by the present invention requires a lower reaction temperature, consumes less energy, and has higher safety.
[0012] (2) The present invention introduces hexadecyltrimethylammonium bromide into the solvent thermal system to control the growth of yttrium fluoride crystals, so that the prepared yttrium fluoride nanomaterial has a good rod-like structure. At the same time, Tween 80 is introduced into the solvent thermal system. The combination of Tween 80 and hexadecyltrimethylammonium bromide can reduce the surface energy and promote the formation of yttrium fluoride crystals.
[0013] (3) The present invention provides the application of yttrium fluoride nanomaterials as negative electrode materials for lithium-ion batteries. The battery assembled with yttrium fluoride as the negative electrode active material can achieve a specific capacity growth rate of 507%, showing relatively excellent electrochemical properties, which provides support for the development of yttrium fluoride nanomaterials as negative electrode materials for lithium-ion batteries. BRIEF DESCRIPTION OF THE DRAWINGS
[0014] In order to more clearly illustrate the embodiments of the present application or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments recorded in the present application. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.
[0015] Figure 1 is the XRD pattern of the yttrium fluoride nanomaterial prepared in Example 1 of the present invention;
[0016] Figure 2 is an EDS image of the yttrium fluoride nanomaterial prepared in Example 1 of the present invention;
[0017] Figure 3 is a SEM image of the yttrium fluoride nanomaterial prepared in Example 1 of the present invention;
[0018] Figure 4 is a TEM image of the yttrium fluoride nanomaterial prepared in Example 1 of the present invention;
[0019] Figure 5This is the constant current charge and discharge curve of the battery prepared in Example 11 of the present invention using yttrium fluoride nanomaterial as the negative electrode active material at 0.1 A / g. DETAILED DESCRIPTION
[0020] The technical solution of the present invention is further described in detail below in conjunction with several preferred embodiments. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present invention.
[0021] The present invention provides a method for preparing an yttrium fluoride nanomaterial, comprising:
[0022] At least a yttrium source and a fluorine source are subjected to a solvothermal reaction at 100 to 140° C. to obtain a yttrium fluoride nanomaterial to be purified;
[0023] The yttrium fluoride nanomaterial to be purified is calcined at 240° C. to 400° C. in a protective atmosphere to obtain the yttrium fluoride nanomaterial.
[0024] In some embodiments, the solvothermal reaction is performed after the yttrium source, the fluorine source and the organic solvent are fully mixed to form a mixed reaction system.
[0025] In some embodiments, the solvothermal reaction is performed after the yttrium source, the fluorine source, the surfactant and the organic solvent are fully mixed to form a mixed reaction system.
[0026] Furthermore, the reaction temperature of the solvothermal reaction is preferably 120° C. The calcination temperature is preferably 240° C.
[0027] In some embodiments, the organic solvent comprises Tween 80 and anhydrous ethanol in a volume ratio of 1:15 to 4:15.
[0028] In some embodiments, the mixed reaction system contains 0.059-0.18 mol / L of a surfactant.
[0029] In some embodiments, the surfactant includes cetyltrimethylammonium bromide.
[0030] In some embodiments, the solvothermal reaction time is 6 to 10 hours. Furthermore, the solvothermal reaction time is 8 hours.
[0031] In some embodiments, the calcination time is 1.5 to 6 hours. Furthermore, the calcination time is 3 hours.
[0032] In some embodiments, the gas used to form the protective gas atmosphere includes nitrogen or an inert gas, more preferably argon.
[0033] In some embodiments, the molar ratio of the yttrium source to the fluorine source is 1:86.25-105.5.
[0034] In some embodiments, the yttrium source includes but is not limited to yttrium nitrate and / or yttrium acetate.
[0035] In some embodiments, the fluorine source includes but is not limited to hydrofluoric acid and / or ammonium fluoride. Hydrofluoric acid is further preferred. Compared with ammonium fluoride and other ionic liquids, hydrofluoric acid has low cost and contains abundant fluorine ions that can directly react to generate the required metal fluoride, which is easier to achieve in industrial production.
[0036] The invention provides yttrium fluoride nanomaterial prepared by the preparation method.
[0037] Furthermore, the yttrium fluoride nanomaterial is a rod-shaped structure. Furthermore, the diameter of the rod-shaped structure is 50-100nm, the length range is 50nm-1μm, and the purity is 99-100%. The rod-shaped structure can increase the contact area between the yttrium fluoride nanomaterial and the electrolyte, making the electrochemical reaction more sufficient and complete, thereby increasing the specific capacity of the negative electrode.
[0038] The present invention provides application of the yttrium fluoride nanomaterial in preparing lithium ion batteries.
[0039] The present invention provides a negative electrode material for a lithium ion battery, wherein the negative electrode material comprises the yttrium fluoride nanomaterial.
[0040] In the following examples, unless otherwise specified, the reagents and raw materials used were purchased directly from commercial channels.
[0041] Example 1
[0042] 1.54 g of yttrium nitrate hexahydrate and 1.46 g of hexadecyltrimethylammonium bromide were added to a mixed solution consisting of 4 mL of Tween 80 and 30 mL of anhydrous ethanol, and magnetically stirred for 1 hour; 15 mL of HF with a mass fraction of 40% was added to the mixed solution, and stirring was continued for 0.5 hour; the mixed solution was then poured into a 100 mL reactor and reacted at 100° C. for 8 hours; after cooling to room temperature, the mixture was centrifuged and washed, and placed in a vacuum drying oven at 120° C. for 3 hours to obtain yttrium fluoride nanomaterial to be purified;
[0043] The yttrium fluoride nanomaterial to be purified was calcined at 240° C. for 3 h in a tubular furnace filled with argon to obtain the yttrium fluoride nanomaterial.
[0044] Figure 1 is the XRD pattern of the yttrium fluoride nanomaterial prepared in Example 1. Figure 1It can be seen that the XRD spectrum of the product prepared in Example 1 corresponds to the standard spectrum (PDF card 74-0911), indicating that yttrium fluoride is successfully prepared. In addition, no diffraction peaks of other products or phases are found in the XRD spectrum, indicating that the purity of yttrium fluoride after calcination and impurity removal is high. Figure 2 is the EDS image of the yttrium fluoride nanomaterial prepared in Example 1. Figure 2 It can be seen that the atomic ratio of Y to F is 1:3, which further proves that the calcined yttrium fluoride nanomaterial has a high purity, with a purity between 99 and 100%. Figure 3 , Figure 4 They are the SEM and TEM images of the yttrium fluoride prepared in Example 1, Figure 3 and Figure 4 The size of the prepared yttrium fluoride is in the nanometer range, and it presents a distinct rod-like structure. The diameter of the rod-like structure ranges from 50 to 100 nm, and the length ranges from 50 nm to 1 μm. This nanorod-like structure has a large specific surface area. When used to prepare the negative electrode of a battery, it is beneficial to increase the contact area with the electrolyte, making the electrochemical reaction more sufficient and complete, thereby increasing the specific capacity of the negative electrode of the battery.
[0045] Example 2
[0046] 1.54 g of yttrium nitrate hexahydrate and 1.46 g of hexadecyltrimethylammonium bromide were added to a mixed solution consisting of 4 mL of Tween 80 and 30 mL of anhydrous ethanol, and magnetically stirred for 1 hour; 15 mL of HF with a mass fraction of 40% was added to the mixed solution, and stirring was continued for 0.5 hour; the mixed solution was then poured into a 100 mL reactor and reacted at 120° C. for 8 hours; after cooling to room temperature, the mixture was centrifuged and washed, and placed in a vacuum drying oven at 120° C. for 3 hours to obtain the yttrium fluoride nanomaterial to be purified;
[0047] The yttrium fluoride nanomaterial to be purified was calcined at 240° C. for 3 h in a tubular furnace filled with argon to obtain the yttrium fluoride nanomaterial.
[0048] Example 3
[0049] 1.54 g of yttrium nitrate hexahydrate and 1.46 g of hexadecyltrimethylammonium bromide were added to a mixed solution consisting of 4 mL of Tween 80 and 30 mL of anhydrous ethanol, and magnetically stirred for 1 hour; 15 mL of HF with a mass fraction of 40% was added to the mixed solution, and stirring was continued for 0.5 hour; the mixed solution was then poured into a 100 mL reactor and reacted at 140° C. for 8 hours; after cooling to room temperature, the mixture was centrifuged and washed, and placed in a vacuum drying oven at 120° C. for 3 hours to obtain the yttrium fluoride nanomaterial to be purified;
[0050] The yttrium fluoride nanomaterial to be purified was calcined at 240° C. for 3 h in a tubular furnace filled with argon to obtain the yttrium fluoride nanomaterial.
[0051] Example 4
[0052] 1.54 g of yttrium nitrate hexahydrate and 1.46 g of hexadecyltrimethylammonium bromide were added to a mixed solution consisting of 4 mL of Tween 80 and 30 mL of anhydrous ethanol, and magnetically stirred for 1 hour; 15 mL of HF with a mass fraction of 40% was added to the mixed solution, and stirring was continued for 0.5 hour; the mixed solution was then poured into a 100 mL reactor and reacted at 120° C. for 6 hours; after cooling to room temperature, the mixture was centrifuged and washed, and placed in a vacuum drying oven at 120° C. for 3 hours to obtain the yttrium fluoride nanomaterial to be purified;
[0053] The yttrium fluoride nanomaterial to be purified was calcined at 240° C. for 3 h in a tubular furnace filled with argon to obtain the yttrium fluoride nanomaterial.
[0054] Example 5
[0055] 1.54 g of yttrium nitrate hexahydrate and 1.46 g of hexadecyltrimethylammonium bromide were added to a mixed solution consisting of 4 mL of Tween 80 and 30 mL of anhydrous ethanol, and magnetically stirred for 1 hour; 15 mL of HF with a mass fraction of 40% was added to the mixed solution, and stirring was continued for 0.5 hour; the mixed solution was then poured into a 100 mL reactor and reacted at 120° C. for 8 hours; after cooling to room temperature, the mixture was centrifuged and washed, and placed in a vacuum drying oven at 120° C. for 3 hours to obtain the yttrium fluoride nanomaterial to be purified;
[0056] The yttrium fluoride nanomaterial to be purified was calcined at 240° C. for 3 h in a tubular furnace filled with argon to obtain the yttrium fluoride nanomaterial.
[0057] Example 6
[0058] 1.54 g of yttrium nitrate hexahydrate and 1.46 g of hexadecyltrimethylammonium bromide were added to a mixed solution consisting of 4 mL of Tween 80 and 30 mL of anhydrous ethanol, and magnetically stirred for 1 hour; 15 mL of HF with a mass fraction of 40% was added to the mixed solution, and stirring was continued for 0.5 hour; the mixed solution was then poured into a 100 mL reactor and reacted at 120° C. for 10 hours; after cooling to room temperature, the mixture was centrifuged and washed, and placed in a vacuum drying oven at 120° C. for 3 hours to obtain the yttrium fluoride nanomaterial to be purified;
[0059] The yttrium fluoride nanomaterial to be purified was calcined at 240° C. for 3 h in a tubular furnace filled with argon to obtain the yttrium fluoride nanomaterial.
[0060] Example 7
[0061] 1.54 g of yttrium nitrate hexahydrate and 1.46 g of hexadecyltrimethylammonium bromide were added to a mixed solution consisting of 4 mL of Tween 80 and 30 mL of anhydrous ethanol, and magnetically stirred for 1 hour; 15 mL of HF with a mass fraction of 40% was added to the mixed solution, and stirring was continued for 0.5 hour; the mixed solution was then poured into a 100 mL reactor and reacted at 120° C. for 8 hours; after cooling to room temperature, the mixture was centrifuged and washed, and placed in a vacuum drying oven at 120° C. for 3 hours to obtain the yttrium fluoride nanomaterial to be purified;
[0062] The yttrium fluoride nanomaterial to be purified was calcined at 200° C. for 3 h in a tubular furnace filled with argon to obtain the yttrium fluoride nanomaterial.
[0063] Example 8
[0064] 1.54 g of yttrium nitrate hexahydrate and 1.46 g of hexadecyltrimethylammonium bromide were added to a mixed solution consisting of 4 mL of Tween 80 and 30 mL of anhydrous ethanol, and magnetically stirred for 1 hour; 15 mL of HF with a mass fraction of 40% was added to the mixed solution, and stirring was continued for 0.5 hour; the mixed solution was then poured into a 100 mL reactor and reacted at 120° C. for 8 hours; after cooling to room temperature, the mixture was centrifuged and washed, and placed in a vacuum drying oven at 120° C. for 3 hours to obtain the yttrium fluoride nanomaterial to be purified;
[0065] The yttrium fluoride nanomaterial to be purified was calcined at 300° C. for 3 h in a tubular furnace filled with argon to obtain the yttrium fluoride nanomaterial.
[0066] Example 9
[0067] 1.54 g of yttrium nitrate hexahydrate and 1.46 g of hexadecyltrimethylammonium bromide were added to a mixed solution consisting of 4 mL of Tween 80 and 30 mL of anhydrous ethanol, and magnetically stirred for 1 hour; 15 mL of HF with a mass fraction of 40% was added to the mixed solution, and stirring was continued for 0.5 hour; the mixed solution was then poured into a 100 mL reactor and reacted at 120° C. for 8 hours; after cooling to room temperature, the mixture was centrifuged and washed, and placed in a vacuum drying oven at 120° C. for 3 hours to obtain the yttrium fluoride nanomaterial to be purified;
[0068] The yttrium fluoride nanomaterial to be purified was calcined at 240° C. for 1.5 h in a tubular furnace filled with argon to obtain the yttrium fluoride nanomaterial.
[0069] Example 10
[0070] 1.54 g of yttrium nitrate hexahydrate and 1.46 g of hexadecyltrimethylammonium bromide were added to a mixed solution consisting of 4 mL of Tween 80 and 30 mL of anhydrous ethanol, and magnetically stirred for 1 hour; 15 mL of HF with a mass fraction of 40% was added to the mixed solution, and stirring was continued for 0.5 hour; the mixed solution was then poured into a 100 mL reactor and reacted at 120° C. for 8 hours; after cooling to room temperature, the mixture was centrifuged and washed, and placed in a vacuum drying oven at 120° C. for 3 hours to obtain the yttrium fluoride nanomaterial to be purified;
[0071] The yttrium fluoride nanomaterial to be purified was calcined at 240° C. for 6 hours in a tubular furnace filled with argon to obtain the yttrium fluoride nanomaterial.
[0072] Embodiment 11
[0073] The positive electrode sheet of the battery was prepared using the yttrium fluoride nanomaterial prepared in Example 1 as the negative electrode active material, with a coating thickness of 100 μm, a drying time of 12 h, a rolling pressure of 10 MPa, and a rolling time of 5 min. A lithium sheet was used as the positive electrode sheet, 1 M LiPF6 was used as the electrolyte (LiPF6 was dissolved in a mixed solution of ethylene carbonate, diethyl carbonate and dimethyl carbonate in a volume ratio of 1:1:1), and Celgard 2500 was used as the diaphragm to assemble the button battery.
[0074] The assembled battery was tested for performance, with a voltage window range of 0.01-3V, a current density of 0.1A / g, and a cycle number of 2000. Figure 5 It can be seen that the lowest specific capacity is 29.3mAh / g and the highest specific capacity is 148.5mAh / g during the 2000 cycles at a current density of 0.1A / g, that is, the growth rate of the specific capacity during the cycle can reach 507%. The significant increase in the specific capacity is due to the following reasons: as the cycle progresses, yttrium fluoride is further nano-sized, its size is further reduced, and more active sites are exposed, which promotes the growth of the specific capacity; as the cycle progresses, the irreversible specific capacity is released during the cycle; and the space charge storage effect takes effect during the cycle.
[0075] The various aspects, embodiments, features and examples of the present invention should be considered as illustrative in all aspects and are not intended to limit the present invention, the scope of the present invention is defined only by the claims. Other embodiments, modifications and uses will be apparent to those skilled in the art without departing from the spirit and scope of the claimed invention.
[0076] In addition, the inventors of this case also referred to the aforementioned embodiments and conducted experiments with other raw materials, process operations, and process conditions described in this specification, and obtained relatively ideal results.
[0077] Although the present invention has been described with reference to illustrative embodiments, it will be appreciated by those skilled in the art that various other changes, omissions and / or additions may be made without departing from the spirit and scope of the present invention and that the elements of the embodiments may be replaced by substantial equivalents. In addition, many modifications may be made without departing from the scope of the present invention to adapt specific circumstances or materials to the teachings of the present invention. Therefore, it is not intended herein to limit the present invention to the disclosed specific embodiments for performing the present invention, but it is intended that the present invention will include all embodiments within the scope of the appended claims. In addition, unless specifically stated, any use of the terms first, second, etc. does not indicate any order or importance, but rather uses the terms first, second, etc. to distinguish one element from another.
Claims
1. A method for preparing yttrium fluoride nanomaterial, characterized in that: include: Fully mixing a yttrium source, a fluorine source, a surfactant and an organic solvent to form a mixed reaction system, and subjecting the mixed reaction system to a solvothermal reaction at 100-140° C. to obtain a yttrium fluoride nanomaterial to be purified; calcining the yttrium fluoride nanomaterial to be purified at 240° C. to 400° C. in a protective atmosphere to obtain the yttrium fluoride nanomaterial; Wherein, the surfactant includes hexadecyltrimethylammonium bromide with a concentration of 0.059~0.18 mol / L; the organic solvent includes Tween 80 and anhydrous ethanol in a volume ratio of 1:15~4:15; the yttrium source includes yttrium nitrate and / or yttrium acetate, the fluorine source includes hydrofluoric acid and / or ammonium fluoride, and the molar ratio of the yttrium source to the fluorine source is 1:86.25~105.
5.
2. The method for preparing yttrium fluoride nanomaterial according to claim 1, characterized in that: The reaction time of the solvothermal reaction is 6 to 10 h.
3. The method for preparing yttrium fluoride nanomaterial according to claim 1, characterized in that: The calcination time is 1.5 to 6 h.
4. The method for preparing yttrium fluoride nanomaterial according to claim 1, characterized in that: The protective atmosphere comprises nitrogen.
5. The method for preparing yttrium fluoride nanomaterial according to claim 1, characterized in that: The protective atmosphere includes an inert gas.
6. Use of the yttrium fluoride nanomaterial prepared by the method described in any one of claims 1 to 5 in the preparation of lithium-ion batteries, wherein the yttrium fluoride nanomaterial is a rod-like structure; the diameter of the rod-like structure is 50-100 nm, the length is 50 nm-1 μm, and the purity is 99-100%.
7. A negative electrode material for a lithium ion battery, characterized in that: The negative electrode material comprises a yttrium fluoride nanomaterial prepared by the method described in any one of claims 1 to 5, wherein the yttrium fluoride nanomaterial is a rod-like structure; the rod-like structure has a diameter of 50 to 100 nm, a length of 50 nm to 1 μm, and a purity of 99 to 100%.